Rastreamento de alterações oculares em crianças pré-escolares e escolares no município de Belém, Pará, Brasil - MAIA, Matheus Rocha (2019)
General Objective: Evaluate visual acuity in children in the age group of five (5) to eight (8) years old from Public Schools of the State of Pará. Specific Objectives: Detect early ophthalmological disorders related to low visual acuity; Structure the path to enable the care of children with ophthalmological alterations detected during the research. Methodology: Descriptive cross-sectional study. Children in the age group from five to eight years old of two (2) public schools in Belém, Pará, were submitted to Ophthalmologic Screening through the Snellen Optometric Scale and Questionnaire with the variables Sex, Age, Use of glasses, Visual quality, School performance impairment due to visual impairment, Prior follow-up with ophthalmologist and Family History of wearing glasses and / or strabismus. Students with visual acuity ≤ 0.7 were referred to the specialized medical service for the Ophthalmologic examination. Results: The prevalence of low visual acuity was 27.73%, of which 44.73% had difficulties to follow the classes due to the visual deficit. Conclusion: The Research identified a high prevalence of children with low Visual acuity associated with consequences in the process of learning and visual well-being.